Motor Competence and Sports Practice in Children with Autism Spectrum Disorder: Pilot Study in Gymnastics - Geraldine Quito; Miguel Jacinto; Nuno Amaro; Diogo Monteiro; Rui Matos; Susana Diz; Tânia Mira; Raúl Antunes (Applied Sciences)
The practice of physical activity, exercise, and sports brings various benefits to the general population. However, a few intervention programs involving physical activity and sports have been specifically designed for children with Autism Spectrum Disorder (ASD). The present study aimed to evaluate the effects of implementing a sports program based on gymnastics (specifically trampolines) on the motor skills of children with ASD. The program ran from September to May 2024 (8 months duration) using the Motor Competence Assessment Battery (MCA) as an evaluation tool. It included three typically developing children and three children with ASD, all aged between 4 and 5 years. The program sessions lasted 45 min and took place twice a week. The MCA Battery was administered to assess motor skills before and after the intervention. After the intervention program, significant differences were found only between moments in the Shuttle Run test (pre-intervention ≠ and post-intervention; Bonferroni correction: t = −2.00; p = 0.043; w = 0.33). Based on these results, we can conclude that practicing a sports program based on gymnastics (namely trampolines) can contribute to improving the motor skills of children with ASD.